Multimedia-Based online Test on Indonesian Language Receptive Skills Development. (December 2019) - Sudaryanto, M; Mardapi, D; Hadi, S
Abstract: The need for computer-based assessment provides an opportunity for test takers to maximize performance in solving questions prepared to their measure language skills. Specifically, this study develops receptive skill tests, i.e. listening, reading, and skills competency responding to the rules. Instruments were tested on the test participants who are elementary level students who join Indonesian language courses. The items were analyzed by Rasch model to determine the level of item difficulty. The results showed that the level of difficulty of the items in the normal distribution in accordance with the ability of test participants. Qualitative analysis shows (1) the weaknesses of using Google-form as a receptive skill test tool, such as connection and unstable internet signal even though tested at college level, test takers still record simultaneous material, the search tool used is not qualified hampering the testing process, (2) the advantages of using Google-form as a receptive skill test tool are there is no need to wait for late test takers, test takers have no chance to cheat and it is paperless, (3) the importance of determining starting point and test rules other. The conclusion of this research is the effectiveness of using Google form as a multimedia-based receptive skill tool capable of minimizing the testing procedure.